Proceedings of the 33rd Annual ACM Conference Extended Abstracts on Human Factors in Computing Systems 2015
DOI: 10.1145/2702613.2732843
|View full text |Cite
|
Sign up to set email alerts
|

InTouch Tactile Tales

Abstract: The squeeze of an arm during a tense moment in a story … an absentminded caress on the back of the hand while listening to an engaging tale … the physical presence and interpersonal touch of a loved one can be an important part of reading to a child. However the thrill of the tale is often lost and the intimacy diluted when separated families have to resort to the flatness of a video-call or mobile app to share a bedtime story with their loved one. This project is setting out to create a physical story portal,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Haptic technologies have previously been used to improve meditation by means of vibrating or 'breathing' pillows [5,11]. Handheld pebble devices can enhance remote storytelling to children [15]. Vibrating vests have been shown to enrich story listening [13].…”
Section: Narrated Stories Augmented With Tactile Patternsmentioning
confidence: 99%
“…Haptic technologies have previously been used to improve meditation by means of vibrating or 'breathing' pillows [5,11]. Handheld pebble devices can enhance remote storytelling to children [15]. Vibrating vests have been shown to enrich story listening [13].…”
Section: Narrated Stories Augmented With Tactile Patternsmentioning
confidence: 99%
“…recently echoed these results using a haptic (pneumatically driven) pillow after testing with 129 participants and concluded that haptic devices can be an effective alternative to mindful breathing practices and can reduce anxiety without the need for training or guidance [5]. Massung et al prototyped handheld pebble devices to enhance remote storytelling to children [6]. The devices are paired so that the narrator can send a vibration to the listener's pebble by squeezing his/her pebble device.…”
Section: Background and Related Workmentioning
confidence: 99%